The present-value model of the current account has been rejected: Round up the usual suspects - James M. Nason; John H. Rogers (Federal Reserve Bank of Atlanta, 2003)
Tests of the present-value model of the current account are frequently rejected by the data. Standard explanations rely on the "usual suspects" of nonseparable preferences, shocks to fiscal policy and the world real interest rate, and imperfect international capital mobility. The authors confirm these rejections on postwar Canadian data, then investigate their source by calibrating and simulating alternative versions of a small open economy, real business cycle model. Monte Carlo experiments reveal that, although each of the suspects matters in some way, a "canonical" RBC model moves closest to the data when it features exogenous world real interest rate shocks.
Keywords: 330; Balance of payments; International finance; Econometric models